Electronic horizon: road information used by Energy Management strategies. (15th May 2008) - Kessels, J.T.B.A.; Van Den Bosch, P.P.J.
Road information from a navigation database system is incorporated into existing EM strategies and translated into a preferred reference trajectory for the battery energy. The EM system can schedule energy among different road segments, optimising the energy efficiency of the vehicle. It turns out that, in many driving situations, the potential fuel benefits from the e-horizon are restricted, due to the excellent performance of existing EM strategies. Driving cycles using a larger range of the battery capacity benefit more from an e-horizon. Nevertheless, the potential gains are limited and will decrease if errors appear in the telematics information.